Effect of different doses of whey proteins on muscle strength, body composition and gene expression of mTOR and MuRF-1 in trained Wistar rats - Raphael Furtado Marques; Marcos Roberto Campos de Macedo; Alanna Joselle Santiago Silva; Flavia Castello Branco Vidal; Carlos Eduardo Neves Amorim; Antônio Coppi Navarro; Francisco Navarro (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: The combination of resistance training (RT) and whey protein supplementation (WPS) is widely practiced by both athletes and recreational exercisers to promote muscle growth and increase strength. Objectiveː This study examined the effect of different doses of whey proteins on muscle strength, body composition and gene expression of mTOR and MuRF-1 in trained Wistar rats. Methodsː 80 male Wistar rats were divided into 8-groups (n=10): sedentary control (C), RT-control (TC), groups consuming whey protein at varying doses (W2, W4, and W6; respectively 2/4/6g/kg/day), and groups consuming whey protein at varying doses combined to RT (TW2, TW4, and TW6; respectively 2/4/6g/kg/day). The RT program was conducted for 12 weeks, three days a week, with the training intensity increasing from 50 to 100% of the rats' body weight. The rats receiving the whey supplement via the gavage method based on their body weight. Resultsː Muscle strength significantly increased in all trained groups (p<0.0001), with a more significant increase in the groups RT and WPS combined. In addition, the expression of mTOR was higher in the RT groups compared to the sedentary groups (p<0.01), but supplementation did not yield significant differences. WPS decreased MuRF-1 expression (p<0.01) independently of RT. Conclusionː In conclusion, RT combined with WPS for 12 weeks improved muscle strength. Furthermore, mTOR expression increased in trained rats, but not in sedentary rats who used different doses of WPS. However, WPS at any dose reduced MuRF-1 expression, independently of RT. Higher WPS doses did not enhance observed gains compared to a lower dose.